"'It is not exactly that bad': on the use of the intensifiers this and that in english - Calle-Martín, Javier (My University, 2015)
The intensifying function of the adverbs this and that can be traced back to the 14th century, when they just appeared in combination with gradable scalar adjectives like big ¿ small, good ¿ bad, easy ¿ difficult, etc. The 20th century has witnessed the rapid diffusion of these intensifiers, but not only in terms of occurrence (both in speech and writing) but also in terms of scope, accepting the other types of gradable adjectives, both limit and extreme adjectives (i.e. dead ) together with non-gradable adjectives (Paradis 2001: 50-53; 2008: 1317-318). The present study investigates the use and distribution of these degree modifiers in present-day English with the following objectives: (a) to trace the development of these intensifiers; (b) to analyse the frequency of the construction from a variationist perspective; (c) to cast light on the lexical semantic structure of the right-hand collocates in terms of their mode of construal and their attitudinal features; and (d) to describe their developmental path. The source of evidence for this study comes from the tagged version of the British National Corpus developed by Mark Davis (BNC-BYU).
Keywords: Lingüística - Congresos; Linguistics; Intensifiers; Syntax